Alan Rugman's methodology. Issue 3 (June 2016) - Casson, Mark
Abstract: This paper argues that the intellectual contribution of Alan Rugman reflects his distinctive research methodology. Alan Rugman trained as an economist, and relied heavily on economic principles throughout his work. He believed that one good theory was sufficient for IB studies, and that theory, he maintained, was internalisation theory. He rejected theoretical pluralism, and believed that IB suffered from a surfeit of theories. Alan was a positivist. The test of a good theory was that it led to clear predictions which were corroborated by empirical evidence. Many IB theories, Alan believed, were weak; their proliferation sowed confusion and they needed to be refuted. Alan's interpretation of internalisation was, however, unconventional in some respects. He played down the trade-offs presented in Coase's original work, and substituted heuristics in their place. Instead of analysing internalisation as a context-specific choice between alternative contractual arrangements, he presented it as a strategic imperative for firms possessing strong knowledge advantages. His heuristics did not apply to every possible case, but in Alan's view they applied in the great majority of cases and were therefore a basis for management action.